PENGARUH SOURCE CREDIBILITY, SOURCE ATTRACTIVENESS, E-WOM TERHADAP LOYALTY TO INFLUENCER DAN PURCHASE INTENTION DENGAN TRUST SEBAGAI MEDIASI - Viona Daisy; Lily Purwianti (Universitas Lambung Mangkurat, 2023)
This study aims to determine the effect of source credibility, source attractiveness, and e-WOM on influencer loyalty and purchase intention through trust in beauty influencers. The population in this study are users of social media such as youtube, instagram, and tiktok who also have a desire for online purchase transactions. The sample in this study is social media users who buy products based on reviews from influencers such as tasya farasya, rachel goodard, Marcella febrianne, nanda arsyinta, and suhay salim of 400 woman’s respondents in Indonesia who are spread on social media. The research method uses a non-probability sampling technique with the help of Smart Partial Least Square in the data analysis process. The results of the study found that there was a significant direct and indirect positive relationship between variables in the study.